Integrative bioinformatics analysis to identify the effects of circadian rhythm on Crohn’s disease - Liu, Dan; Chen, Yin-Yun; Li, Qing-qing; Xu, Ming; Liao, Jiang-Tao; Wang, Ben (Frontiers in Molecular Biosciences, 2022)
Background: Crohn’s disease (CD) is a multifactorial inflammatory bowel disease characterized by complex aberrant autoimmune disorders. Currently, the involvement of the circadian rhythm in the pathogenesis of CD is unknown. Methods: Bulk and single-cell RNA-seq data and associated clinical data from patients with CD were downloaded from the Gene Expression Omnibus (GEO). Single-sample gene set enrichment analysis was performed to calculate the enrichment score (ES) of circadian rhythm-related genes. Differential expression analysis was used to identify differentially expressed genes. Functional enrichment analysis was used to explore potential disease mechanisms. CIBERSORT was used to estimate the immune cell abundance. Single-cell RNA-seq data was analyzed using the R package “Seurat.” Results: The ES of circadian rhythm-related genes was lower in the CD tissue compared to that in the normal tissue. Ubiquitin-specific protease 2 (USP2), a circadian rhythm-related gene, was identified as a potential modulator of CD pathogenesis. USP2 expression was reduced in CD and was associated with disease severity. Moreover, the analysis of bulk RNA-seq and single-cell RNA-seq data showed that monocyte and neutrophil abundance was elevated in CD and was negatively correlated with USP2 expression. Notably, USP2 expression in acinar cells was negatively correlated with monocyte and neutrophil abundance. Functional enrichment analysis revealed several canonical pathways to be enriched in CD, including interleukin-17 signaling pathway, tumor necrosis factor signaling pathway, cytokine-cytokine receptor interaction, toll-like receptor signaling pathway, and nod-like receptor signaling pathway. Conclusion: Aberrant expression of circadian rhythm-related genes is correlated with CD pathogenesis. USP2 might be related to crosstalk among the different cell types in CD. These findings provide insights into future chronotherapy for CD.